Molecular, Metabolic, and Physiological Responses to Progressive Biotic Stress Caused by Cucumber Mosaic Virus and Turnip Mosaic Virus in Saffron - Marzieh Shamshiri; Conchi Sánchez; Saleta Rico; Ali Mokhtassi-Bidgoli; Mahdi Ayyari; Hassan Rezadoost; Masoud Shams-Bakhsh (Horticulturae)
The economic value of the saffron stigma is primarily due to three crucial apocarotenoids: crocin, picrocrocin, and safranal, which contribute to its color, flavor, and aroma. These compounds make saffron highly valuable in various industries. Plant viruses like the cucumber mosaic virus (CMV) and turnip mosaic virus (TuMV) are significant threats to agricultural crops worldwide, causing economic losses. To elucidate the influence of viral stress on the quality of saffron, morphological, physiological, biochemical, and molecular indexes were assessed. Under the stress of both viruses, typical viral symptoms appeared. The lowest contents of leaf pigments, flowering performance, petal anthocyanin, greenness, and photosynthesis properties were observed in plants infected with CMV and TuMV. According to high-performance liquid chromatography (HPLC) analysis, CMV inoculation led to the highest reduction in crocin and safranal content, while inducing the highest increase in picrocrocin compared to the mock treatment. Gene expression analysis involved in the biosynthesis of crucial secondary metabolites showed a high correlation with the content of each metabolite. CMV inoculation resulted in the lowest expression of CsALDH31l and the highest expression of CsUGT709G1 compared with the mock treatment. Our findings demonstrate the association between virus stress and changes in the metabolism of the saffron medicinal plant.